7.7-kW Inductive Coupling Three-Phase Coil Wireless Power Transfer Pads for Electric Vehicles Charging - Mahesh Aganti; Bharatiraja Chokkalingam; Rajesh Verma; Lucian Mihet-Popa (IEEE Access)
Modern electric vehicle (EV) wireless charging systems (WCSs) rely heavily on Resonant Inductive Power Transfer (RIPT), which offers a flawless integration of safety, dependability, and automated functionality. In RIPT-based WCS, the design of magnetic pads is a critical factor that significantly influences power transfer efficiency. This component is essential for optimizing the system’s performance. Three-phase couplers (TPCs) surpass single-phase designs by offering higher energy transfer capacity, along with benefits such as rotating magnetic flux and lessened use of ferrite materials. This article provides an in-depth analysis of a TPC with a circular design, referred to as the “Three Half Circular Coil” (3HCC) pad. Three half-circular coils are positioned in a circle to form the 3HCC pad, delivering advantages such as improved angular misalignment tolerance, optimized ferrite utilization, and simplified construction. The effectiveness of the 3HCC design is evaluated using Matlab and FEA tools for a 7.7 kW WCS, with comparisons made against tripolar, three-phase rectangular, and traditional single-phase circular coil designs. To validate the 3HCC design, a 7.7 kW lab prototype was developed, focusing on coupling and cross-coupling effects influenced by various coil attributes like misalignment, coil position, and the number of turns. The research emphasizes the vital role of RIPT in EV charging and demonstrates the superiority of TPCs compared to their single-phase equivalents. Furthermore, it demonstrates the proposed 3HCC design’s effectiveness in improving charging efficiency.